Improving senior high school students’ vocabulary mastery through short stories at SMAN 11 Bandar Lampung class X in the 2024/2025 academic year - Manik, Tiur Paulina; Sutarsyah, Cucu; Kadaryanto, Budi (English Language Education Study Program, 2025)
Vocabulary acquisition plays a vital role in language learning, yet many high school students struggle to expand their vocabulary effectively. This study investigates whether there is a significant difference in students’ vocabulary improvement after being taught using short stories. Conducted at SMAN 11 Bandar Lampung with tenth-grade students. This study employs a quasi-experimental design with a pretest and post-test to measure students' vocabulary size before and after the intervention. A total of 35 students participates in the study, receiving vocabulary instruction through selected short stories. The Vocabulary Size Test (VST) assesses students' vocabulary mastery across six word-frequency levels. The findings indicate a significant improvement in students’ vocabulary knowledge after the intervention. It is shown on the mean score of pre-test 2707 while the mean score of post-test 3610 which means higher than pre-test. The most substantial improvement appears in mid-frequency vocabulary (Third 1,000 to Fifth 1,000 levels), while gains in higher-level vocabulary (Sixth 1,000 level) are relatively lower. The conclusion is drawn based on the results obtained from the paired sample T-test. The significant sig. (2-tailed) of pre-test and post-test 0.000. The sig. (2- tailed) is 0.000 < 0.05 which means the pre-test and post-test has sig < a and can be concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. From these findings, there is an improvement in vocabulary mastery and it is concluded that using Short Stories can improve vocabulary mastery.